PERAN LAYANAN INFORMASI GUNA MENINGKATAKAN MOTIVASI BELAJAR SISWA DI SMPN 282 JAKARTA - Puspa, Zavira Dwi; Nurmawati, Nurmawati (LPPM Institut Pendidikan Nusantara Global, 2023)
It is easy to find that there are some who experience difficulties in the learning process of their students in class, all of which are influenced by the low learning motivation that students have. Motivation itself has a very important role in the process of student learning activities. But sometimes student motivation can decrease due to several factors, both internal and external. There are several guidance and counseling services, one of which is information services. Where this information service itself can be provided to students in order to provide information about the problems experienced by students. The research conducted has the objectives of: 1) Knowing the role of information services to increase students' learning motivation at SMPN 282 Jakarta with student learning motivation, 2) Obstacles in the implementation of information service activities at SMPN 282 Jakarta, 3) The reality of students' learning motivation at SMPN 282 Jakarta. Data collection techniques in this study, using observation and interviews. This research was also conducted with a descriptive descriptive type of research, with the support of some literature study materials. therefore, the research data that researchers get will be strong. The results of this study show that: 1) Guidance and Counseling teachers plan information services by adjusting students' needs, 2) There is involvement of the teacher/homeroom teacher and the school in the implementation of information services, 3) The form of the reality of learning motivation carried out by students in school. What can be found is that information services can increase students' learning motivation at SMPN 282 Jakarta